Algoritma ROC dan MOORA dalam Pencarian Buku di Perpustakaan Umum Kabupaten Labuhanbatu - Putri, Pebriani; Hasugian, Abdul Halim (Program Studi Teknik Informatika Universitas Pamulang, 2024)
The public library is a common facility with thousands of book collections. In public libraries, visitors often encounter difficulties in finding the books they desire, and it's not uncommon for them to leave without locating their desired reads. To address this issue, the researcher proposes a system that includes book information and analytical tools to determine the most favored books in the library. In this study, the researcher applies the ROC and MOORA methods to develop a Decision Support System (DSS) for identifying the most preferred book choices, enabling the library to acquire books based on visitors' preferences. Four criteria are considered: book genre, number of book borrowings, popularity, and book availability. Testing is conducted by comparing six book data sets, with the research revealing that alternative data A1